A new species of Moenkhausia Eigenmann (Characiformes: Characidae) from the upper rio Juruena basin, Central Brazil - Dagosta, Fernando C. P.; Marinho, Manoela M. F.; Benine, Ricardo C. (Zootaxa, 2015)
Moenkhausia lineomaculata, new species, is described herein from the upper rio Juruena, upper rio Tapajós basin. The new species seems to be part of a monophyletic group formed by M. cosmops, M. cotinho, M. diktyota, M. forestii, M. oligolepis, M. sanctaefilomenae, and M. pyrophthalma, the Moenkhausia oligolepis/M. sanctaefilomenae complex, by sharing a reticulated color pattern on body and the presence of a light area preceding a wide, dark caudal-peduncle blotch. The new species is distinguished from these species, except M. cotinho, by the presence of longitudinal series of dark dots on body, and from M. cotinho by the humeral blotch evenly pigmented along its length and by having the dark line along horizontal septum starting approximately at the vertical through dorsal-fin origin. The new species presents intraspecific variation in lateral-line scales perforation, a feature often present in species of the aforementioned group.